2018
DOI: 10.1007/s10815-018-1165-x
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin serum levels following ovulation triggering and IVF cycle outcome

Abstract: hCG levels on the day after ovulation triggering with 250 mcg r-hCG are inversely correlated with patient age and BMI. However, they are not correlated with any clinical or laboratory outcome parameter. Therefore, testing for hCG levels after ovulation induction seems futile and cannot be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
2
7
0
3
Order By: Relevance
“…Although the biological significance, if any, of the differences in LH (day 5 after trigger) and progesterone levels (36 h after trigger) observed between the two BMI groups is unknown, it seems that triggering final oocyte maturation with 0.2 mg triptorelin elicits a different hormonal profile in the luteal phase in patients classified into the two BMI groups. It may be speculated that BMI could play a role in triptorelin clearance or GnRH-receptor binding, similar to previous findings in the case of triggering final oocyte maturation with HCG (Detti et al, 2007;Mizrachi et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although the biological significance, if any, of the differences in LH (day 5 after trigger) and progesterone levels (36 h after trigger) observed between the two BMI groups is unknown, it seems that triggering final oocyte maturation with 0.2 mg triptorelin elicits a different hormonal profile in the luteal phase in patients classified into the two BMI groups. It may be speculated that BMI could play a role in triptorelin clearance or GnRH-receptor binding, similar to previous findings in the case of triggering final oocyte maturation with HCG (Detti et al, 2007;Mizrachi et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…It has previously been shown that serum HCG levels, measured after HCG injection, are significantly inversely associated with patient BMI (Detti et al, 2007;Mizrachi et al, 2018). These findings suggest that the patient's BMI may be a major determinant of HCG clearance in the body and could possibly help in optimizing HCG dose used for triggering final oocyte maturation.…”
Section: Introductionmentioning
confidence: 93%
“…Έχει αποδειχθεί ότι σε γυναίκες που λαμβάνουν hCG, για επαγωγή της τελικής ωρίμανσης των ωαρίων, η συγκέντρωση hCG ορού συσχετίζεται αρνητικά με το ΔΜΣ της ασθενούς (Detti, et al, 2007, Mizrachi, et al, 2018 5 Σύνδρομο υπερδιέγερσης ωοθηκών Το ΣΥΩ είναι μια συστηματική νόσος, η οποία ότι προκύπτει από απελευθέρωση αγγειοδραστικών πεπτιδίων από τα κοκκώδη κύτταρα σε ωοθήκες που έχουν υποστεί διέγερση . Η θεμελιώδης μεταβολή στο σοβαρό ΣΥΩ, είναι η αύξηση της αγγειακής διαπερατότητας, με αποτέλεσμα τη μετατόπιση υγρού από τον ενδοαγγειακό χώρο στην περιτοναϊκή και θωρακική κοιλότητα.…”
Section: διατήρηση της μειωτικής παύσηςunclassified
“…Αυτό έχει ως αποτέλεσμα το γεγονός ότι, η επαγωγή με GnRHa οδηγεί σε σχεδόν πλήρη εξάλειψη του πρώιμου σοβαρού ΣΥΩ, εάν εφαρμοστεί η στρατηγική κατάψυξης όλων των εμβρύων (Youssef, et al, 2014). Μπορεί να θεωρηθεί ότι, ο ΔΜΣ θα μπορούσε να διαδραματίσει κάποιο ρόλο στην απορρόφηση της τριπτορελίνης ή στη δέσμευση του υποδοχέα GnRH, όπως έχει αποδειχθεί και προηγουμένως στην περίπτωση της επαγωγής με hCG (Detti, et al, 2007, Mizrachi, et al, 2018 12 Σύνθεση και κριτική αξιολόγηση των δεδομένων Αν και ο συνηθέστερα χρησιμοποιούμενος GnRH αγωνιστής, για την επαγωγή της τελικής ωρίμανσης των ωαρίων, σε ασθενείς που υποβάλλονται σε διέγερση των ωοθηκών για εξωσωματική γονιμοποίηση είναι η τριπτορελίνη (Fauser, et al, 2002, Humaidan, et al, 2011, τα δεδομένα σχετικά με τη βέλτιστη δόση είναι επί του παρόντος περιορισμένα.…”
Section: περιγραφή των μετρούμενων παραμέτρωνunclassified
See 1 more Smart Citation